Colombia : Report on the Observance of Standards and Codes-Data Module. (IMF Staff Country Reports; Country Report ;, 2006)
The quality of the macroeconomic statistics is generally high, broadly conforming to international standards for compilation and dissemination, although coverage of illicit activities is poor. Executive Directors suggest reviewing the legal framework for statistical activity, including strengthening the institutional and financial independence of the National Administrative Department of Statistics. Further strengthening is needed in the areas of national accounts and government finance statistics. Developing a methodology to include unrecorded trade in the balance of payments on a timely basis is also required.